Victimization After Meeting With Online Acquaintances: A Cross-Sectional Survey of Adolescents in Malaysia - Marret, Mary Joseph; Choo, Wan Yuen (SAGE Publications, 2018)
This study aimed to determine contact and privacy risks encountered by Malaysian adolescents with access to the Internet and mobile phones and factors associated with face-to-face meetings with online acquaintances as well as to estimate the prevalence of subsequent victimization. Secondary school students from randomly selected public schools in Selangor and Kuala Lumpur responded to an anonymous self-administered questionnaire (78% response rate). Out of 3,349 Internet or mobile phone users, 51% had been invited to meet offline with an online-meeting acquaintance and 30% complied. Of the 1,005 respondents who went to offline meetings, 55% had meetings with more than six people. Male gender, Malay ethnicity, online access at an Internet café, viewing pornography on the Internet, the absence of parental restrictions on visiting certain website and chat rooms, not being explicitly forbidden to meet strangers encountered online, and disclosure of personal information were significantly associated with increased odds of face-to-face meetings with online acquaintances. Verbal, physical, or sexual assaults were reported by 5.5% of the 1,005 including 13 males and five females who reported forced sexual intercourse. Similarities as well as differences in factors associated with risk-taking behavior compared with adolescents in Western countries have important implications on policy and intervention.